Illness perceptions in patients and parents in paediatric oncology during acute treatment and follow‐up care. Issue 6 (27th January 2022) - Herzog, Kristina; Schepper, Florian; Kamm, Remo; Engelhardt‐Lohrke, Christa; Kreisch, Andrea; Pletschko, Thomas; Hauer, Julia; Christiansen, Holger; Suttorp, Meinolf; Kiel, Julia; Martini, Julia
Abstract: Objective: Recent evidence suggests that illness perceptions in paediatric patients and their parents may differ, with parents holding more negative views compared to their children. Little is known about illness perceptions of very young patients and their parents. This study investigates illness perceptions in paediatric cancer patients aged 4–18 years and their parents in acute treatment or follow‐up care, distinguishing patients by age (4–11, 12–18) and stage of medical treatment. Methods: N = 45 patient–parent dyads in acute treatment and n = 95 dyads in follow‐up care were examined. Parents and older children aged 12–18 years completed the Illness Perception Questionnaire—Revised (IPQ‐R) and younger children aged 4–11 years were examined using an age‐adapted hand puppet interview containing the IPQ‐R questions. Difference scores of illness perceptions (symptoms, timeline‐acute/chronic, timeline‐cyclical, personal control, illness coherence, consequences, emotional representations) between children and parents were tested for significance using Wilcoxon signed‐rank tests. Results: Overall, parents perceived more symptoms associated with their child's illness/treatment than the children themselves. In acute treatment, younger children indicated more negative and older children more positive views regarding chronicity than parents. Younger children held less negative views on consequences, and all children reported less negative emotional representations than parents. In follow‐up care, all children held less negative views on consequences and emotional representations. Older children reported less negative views on chronicity, cyclicity and illness coherence. Conclusion: Differences in illness perceptions of paediatric patients and their parents should be considered during and after treatment/medication and psychosocial care to support illness coping in person‐ and family‐centred interventions.